European Union implementation of Article 5.3 of the Framework Convention on Tobacco Control - Benjamin Hawkins; Chris Holden (BMC, 2018)
Abstract Background Article 5.3 of the World Health Organization's Framework Convention on Tobacco Control (FCTC) requires Parties to the agreement to take proactive measures to protect health policy from the vested interests of the tobacco industry. Parties to the FCTC are required to submit periodic reports to the Convention Secretariat on the efforts undertaken to implement it. Previous analyses of national compliance with the FCTC suggest that Article 5.3 implementation is piecemeal and insufficient in many contexts, with governments relying on general transparency and other existing policies for the purpose of Article 5.3 implementation. No in-depth study of Article 5.3 compliance within the European Union (EU) - a signatory to the Convention - has been undertaken. This study seeks to assess the extent of Article 5.3 compliance in European Union institutions, through an analysis of the mechanisms in place in the European Commission and European Parliament. It analyses EU documents relevant to Article 5.3 compliance, as well as semi-structured interviews with policy actors in the EU institutions and the field of tobacco control. Results As with many national governments, Article 5.3 compliance within EU institutions is partial and incomplete. Much of the compliance activity cited in EU reports is derived from general codes of conduct for EU staff and the Juncker Commission's transparency agenda. Interview respondents reveal widespread lack of knowledge about the existence of the FCTC and Article 5.3 amongst key policy actors across the institutions. Within the Commission policies vary greatly between Directorates General, and issues surrounding the conceptualisation of the role of Members of the European Parliament affect implementation in that context. While there is growing awareness of the issue in both the Commission and the Parliament, in large part as a result of the experience of lobbying over the Tobacco Products Directive, there remains considerable resistance in both institutions to further substantive action to implement Article 5.3. Conclusions We recommend that a binding and comprehensive policy and code of conduct, specifically designed for the implementation of Article 5.3 and based on the World Health Organization's guidelines, be created to cover the activities of all employees of all EU institutions. Crucially, such guidelines would need to deal explicitly with third parties acting for the tobacco industry.